Agenda-setting on traditional vs social media: An analysis of haze-related content grounded in the extended parallel process model. Issue 4 (5th August 2019) - Chen, Liang; Shi, Jingyuan; Guo, Yu; Wang, Pianpian; Li, Yiwei
Abstract : Purpose: The purpose of this paper is to explore and compare haze-related content between traditional and social media in China by applying agenda-setting theory and the extended parallel process model (EPPM). Specifically, this paper examines the correlation between the two forms of media in terms of the ranking of the attributes of haze (i.e. the EPPM components) and the interrelationships among the attributes. Design/methodology/approach: Content analysis and semantic network analysis were employed to address the research aims. Findings: The results revealed that more than half of the total messages on both types of media reflected the EPPM components, either threat or efficacy information. However, the imbalance between the threat and efficacy information was more prominent in the haze-related content presented in the People's Daily than it was on Weibo. In addition, the results from a Spearman's rank-order correlation and a quadratic assignment procedure (QAP) indicated that there was no significant correlation between the People's Daily and Weibo in terms of the rankings of the attributes of haze (i.e. the EPPM components) or the interrelationships among the attributes. Originality/value: This study is the first to apply a theoretical approach to examine and compare the nature of haze-related messages on traditional and social media.